Let f ( x ) = 3 x 7 + 2 x 2 + 4 x + 1 . Then f is one to one. Use this information to compute ( f − 1 ( 1 ) ) ′ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since f is one to one, we know the following property holds for f and its inverse: f ( f − 1 ( x ) ) = x and differentiating both sides gives f ′ ( f − 1 ( x ) ) ( f − 1 ( x ) ) ′ = 1 ( f − 1 ( x ) ) ′ = f ′ ( f − 1 ( x ) ) 1 and all that remains is to compute f − 1 ( 1 ) . To do this we notice that f ( 0 ) = 1 so it must be that 0 = f − 1 ( 1 ) and since f ′ ( 0 ) = 4 we have ( f − 1 ( 1 ) ) ′ = 4 1
Dr. Moroney that is a most impeccable questions that once again boggles my mind. You're are on roll that is unmatched by anyone else in the mathematical community. I am excited to hear you're lecture at Cambridge University on Nano-Engineering. As always good luck Doctor!
Problem Loading...
Note Loading...
Set Loading...
We note that f ( 0 ) = 1 . Since f is one-to-one, this implies that f − 1 ( 1 ) = 0 . Let y = f ( x ) , then ( f − 1 ( x ) ) ′ = d y d x = d x d y 1 = 2 1 x 6 + 4 x + 4 1 . ⟹ ( f − 1 ( 1 ) ) ′ = d y d x ∣ ∣ ∣ ∣ x = 0 = 4 1 .